Recent advances in enhanced chemodynamic therapy strategies. (August 2021) - Tian, Qiwei; Xue, Fengfeng; Wang, Yurui; Cheng, Yuying; An, Lu; Yang, Shiping; Chen, Xiaoyuan; Huang, Gang
Highlights: The strategies used to improve CDT performance were discussed. The increased production, accelerated generation, and enhanced efficacy of hydroxyl radicals were summarized. The challenges of mechanism of Fenton or Fenton-like reactions in the tumor microenvironment were discussed. Graphical Abstract: The strategies used to improve CDT performance, including the increased production, accelerated generation, and enhanced efficacy of hydroxyl radicals were summarized and discussed. ga1 Abstract: Chemodynamic therapy (CDT) is a novel therapeutic modality that employs Fenton or Fenton-like reactions to destroy cancer cells via the disproportionation of intratumoral hydrogen peroxide (H2 O2 ) to the highly toxic hydroxyl radical (OH) without external energy input. However, the poor effectiveness of CDT has limited its clinical application. Therefore, over the past few years, various strategies have been explored to enhance the efficiency of CDT. In this review, we have provided an overview of the strategies used to improve CDT performance, including the increased production, accelerated generation, and enhanced efficacy of hydroxyl radicals. Furthermore, the challenges and perspectives of emerging and potential CDT techniques are also discussed; this review is expected to stimulate the development of non-invasive and efficacious CDT techniques.